PENYESUAIAN (AGREEMENT) SUBJEK DAN KATA KERJA DALAM BAHASA ANSUS, PAPUA - SARAGIH, YANSEN M.I. (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 15 (2008): March 2008, 2008)
Abstract Ansus is an Austronesian language which is located in the west of Yapen Island. The language is spoken mainly on the village of Ansus, Kairawa and Yemprum on the island of Miosnum. This research is focused on morphology and syntax, especially in agreement between subject and verb in Ansus language. This research is aimed to present the morphosyntax of subject verb agreement in Ansus language. Descriptive method is used in this research. The results of this study are in Ansus Language the agreement is the prefix of the verb phrase and does not happen in second person singular and third person singular as the subject. In addition, the agreements are the prefix e - , u -, mu -, anto -, mito -, ito -, ama -, and me -. Prefix e- is found in the sentence which consists of first person singular as subject. Prefix u- is found in the sentences which consist of first person dual and third person dual as subject. Prefix mu- is found in the sentence which consists of second person dual as subject. Prefix anto-, mito-, ito- are found in the sentences which consist of first person trial, second person trial, and third person trial as subject. Prefix ama- and me- are found in the sentence which consist of first person plural and second person plural as subject.